Periodic colonization of Trichogramma japonicum for bio-control of yellow stem borer (Scirpophaga incertulas) in summer low-land rice (Oryza sativa) - MURALI-BASKARAN, R K; SRIDHAR, J; SHARMA, K C; JAIN, LATA; GHOSH, P K (The Indian Journal of Agricultural Sciences, 2024)
Yellow stem borer [Scirpophaga incertulas (Walker)], is a major pest of low-land rice (Oryza sativa L.), causing 30–40% yield losses. The use of biological control agents to suppress yellow stem borer (YSB) population and damage across Asia includes inundative releases of the egg parasitoid, Trichogramma japonicum Ashmead. However, information on the time and number of parasitoids’ releases are lacking to control YSB in summer low-land rice. Therefore, an experiment was conducted during summer seasons of 2018 and 2019 at ICAR-National Institute of Biotic Stress Management, Raipur, Chhattisgarh to standardize the time and number of T. japonicum releases for effective biocontrol of YSB. Experiment consisted of 3 different treatment schedules, viz. T1, Four releases of T. japonicum at weekly intervals on the 7th, 14th, 21st, 28th days after planting (DAT); T2, Four releases of T. japonicum at weekly intervals on the 14th, 21st, 28th, 35th DAT; T3, Four releases of T. japonicum at weekly intervals on the 21st, 28th, 35th, 42nd DAT; and T4, Control (no release of wasps). Significant reduction of YSB-induced damage symptoms was observed in the treatment schedule (T2) consisting of four releases of T. japonicum (@50,000 wasps/ha/release) at weekly intervals on the 14th, 21st, 28th, 35th DAT of rice which significantly reduced the dead heart (9.1%, 45.83% reduction over control) and the white ear (1.8%, 47.05% reduction over control), as compared to untreated control plots (T4) (16.8% dead heart, 3.4% white ear) in summer 2018. Similarly, in summer 2019, the reduction in dead heart and white ear by the treatment (T2) was 43.35% and 46.15% over control, respectively. The significant reduction of YSB-induced damages corresponded with the increased grain yield in (T2) from 2018–19 i.e. 12.74–20.18% across the seasons. The results suggest that the (T2) augmentative releases provided ecologically viable bio-control of YSB during the summer seasons in low-land rice.